Accountability Policies: Tensions and Difficulties in School Management, a Literature Review - Leiva Guerrero, María Verónica; Donoso Osorio, Elizabeth; Cádiz Altamirano, Marilyn; Díaz Peralta, Enzo (Revista del CLAD Reforma y Democracia, 2022)
An important change in Chilean education in the last decade has been the incorporation of accountability policies and mechanisms, such as the Education Quality Assurance System, the Preferential School Subsidy Law (SEP) and the New Public Education for educational improvement. These prevailing policies are made up of a set of strategic projects belonging to the Ministry of Education, whose purpose is to comprehensively and systemically strengthen the quality of education provided in the country’s schools. In order to know what happens in schools in terms of policy implementation and accountability mechanisms, the objective is to analyze these mechanisms, identifying the main difficulties and tensions reported by the research carried out within the framework of public policy in which educational management is evaluated. In order to achieve this objective, a documentary study was carried out with a systematic descriptive review of research and technical documents published between 2000 and 2020, with emphasis on the concepts of quality, accountability and school management. A deductive content analysis was applied to the 28 articles and documents selected, which describe the tensions and difficulties brought about by accountability policies in Chilean schools. The product of this research clearly identified that the installation of the accountability model, on the one hand, implies a pressure on schools focused on improving their results in terms of goals and deadlines and, on the other hand, reveals the challenge of leadership in decision-making between what is urgent and what is important to achieve these goals. Finally, this quality assurance system, which is framed in an accountability paradigm, mainly from the performative and professional models, brings with it high consequences for schools, where external agencies define the standards of educational efficiency and effectiveness.